Study of physical, sensory and bacteriological properties of cold-preserved luncheon beef meat containing powder of oregano and maui rose - Sajja Adnan Abdul Hamid Al-Zaidan; Khadeeja Sadiq Jaffer Al- Hussainy (Zien Journals, 2023)
This study was conducted in order to study the effect of using different proportions of powders (oregano Origanum vulgare and maui rose Borago officinalis) on the physical, sensory and bacteriological properties of the luncheon product cooling at 4 Cº for periods of (0, 3, 6, 9, 12, 15) days, compared with an industrial oxidation (Butylated Hydroxy Toluene (BHT)) and control treatment, luncheon product was prepared by making seven treatments (control sample devoid of luncheon spices, herbal powder and industrial antioxidant T1, sample treated with luncheon mix seasoning T2, sample treated with industrial antioxidant with 0.02 % of The BHT)) T3, the luncheon sample treated with 0.3% of oregano T4, the luncheon sample treated with 0.5% of oregano T5, the luncheon sample treated with 0.3% of the Mao rose T6, the luncheon sample treated with 0.5% of the maui rose T7).
Keywords: luncheon; oregano; maui rose; numbers of total bacteria